Gestión administrativa en el departamento de talento humano del Gobierno Autónomo Descentralizado Municipal del Cantón Alfredo Baquerizo Moreno (Jujan) - Moyota Garcia, Fabiola Yamilet (2021)
In the present case study called "Administrative Management in the Human Talent Department of the Autonomous Decentralized Municipal Government of the canton Alfredo Baquerizo Moreno (Jujan)" aims to know the administrative management of the area in order to analyze the planning phase, organization, direction and control, which for a year has been performing wrongly. Among them are restructuring of the organization chart, department resources, biometric clock, recruitment and selection process for hiring personnel, training, communication, performance evaluation and for this reason there is a delay in the functions they perform. With the application of the inductive methodology, the collection of new data from primary sources for a specific purpose was obtained, in addition, the type of descriptive research was applied to specify the characteristics of the population, situation or phenomenon around which the study is centered through the Interview with the head, necessary information was acquired within the legal framework through a questionnaire.